THE HEAT TRANSFER AND MAGNETOHYDRODYNAMICS PROBLEM WITH HEAT SOURCE IN HALF INFINITE 1-D DOMAIN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In this paper we consider the temperature and laminar flow of an incompressible conducting fluid past a non-conducting half-space. For the space approximation the finite differences method-finite difference scheme (FDS) and finite difference scheme with exact spectrum (FDSES) for solving the heat transfer and laminar flow initial boundary-value problem are used. This procedure allows reducing the problem to initial value problem for ordinary differential equations and the solution to the problem can be obtained numerically and analytically. The equation of the temperature is un-depending on the velocity and this function we can obtain in analytical form use the integral transform methods- Fourier and Laplace transforms.